THE ROLE OF THE COMMUNITY IN ELECTORAL SUPERVISION MANAGEMENT - Fadli Muhamad, Lili; Agus Hermawan (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2023)
Elections are a fundamental mechanism within the democratic framework, facilitating the selection of leaders and representatives who will be the voice and embodiment of the people. The preservation of integrity and fairness in the conduct of the electoral process is essential to ensure proper representation and foster public confidence in the final outcome. This study aims to explore previous research that has been conducted in the area of public participation in election monitoring and provide in-depth analyses. This study is a qualitative research. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The findings of this study show that the involvement of the general public in the management of election monitoring plays an important role in upholding the principles of integrity, transparency and trust in the electoral system. The public has the opportunity to be actively involved in monitoring, reporting and supervising the conduct of elections through both direct and institutionalised participation mechanisms. Strong public participation can also serve as a mechanism to prevent and detect potential election violations, increase the level of transparency, and improve the credibility of election results.